2016
DOI: 10.1515/genst-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Female Media Producer as an Advocate of Women’s Empowerment in Nigeria: The Cross River State Experience

Abstract: This paper presents an investigation into Nigerian female journalists’ definition of their role vis-à-vis the two concepts of women’s empowerment/emancipation and feminism. It examines the level to which the country’s media and social environment are conducive to feminist journalistic expression. The paper argues that although a good number of female media producers in the country, demonstrate a strong adherence to feminism and women’s empowerment/emancipation, they are hindered from fully materialising their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The exact causes of these variations are difficult to explain in light of the present findings. However, it is assumable that these disparities are the reflection of the deeply ingrained socioeconomic inequalities across different geopolitical regions in the country as depicted by national and internally renowned news media [14, 2426].…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of these variations are difficult to explain in light of the present findings. However, it is assumable that these disparities are the reflection of the deeply ingrained socioeconomic inequalities across different geopolitical regions in the country as depicted by national and internally renowned news media [14, 2426].…”
Section: Discussionmentioning
confidence: 99%
“…Based on all these premises, the act of transposing the western woman situation in a film meant to depict the African woman may be read as unrealistic or inauthentic and a form of cultural synchronization; even if such a cinematic choice is originally aimed at correcting the stereotypical representations of women by male-authored films [5,3]. Tari shares corollaries as she enthuses that, alternative female African filmmakers should thrive towards achieving a "middle ground" where the women will neither be preys for men nor predators.…”
Section: Alternative Feminist Cinema and Realismmentioning
confidence: 99%
“…Though it may be hard to find reliable statistics to mathematically describe women's representation in African cinema, it has generally been assumed or guessed that the situation is worst in Africa, compared to other continents. At least, numerous empirical studies have demonstrated the persistence of negative stereotyping of women in the various African films [3][4][5][6][7][8][9]. In view of this technical and structural anomaly, feminist critics and female African film critics have since advocated the emergence of a feminine alternative cinema which, being feminist/womanist in inclination, will labour to correct the chauvinistic representation of women in the male dominated (mainstream) African cinema.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reducing gender inequality and violence is a global health and development priority (United Nations General Assembly, World Health Organization). Gender inequality affects human health and wellbeing and has severe consequences for women and girls (Uko 2004;Endong 2017).…”
Section: Introductionmentioning
confidence: 99%